RECONTEXTUALIZATION OF SUN WUKONG’S HEROISM IN THE MONKEY KING FILM TRILOGY 2014–2018 - Wulandari, Adi Kristina; Budiman, Manneke; Wuryandari, Nurni Wahyu; Rusdiarti, Suma Riella (Paradigma: Jurnal Kajian Budaya, 2023)
The classic Chinese novel, Journey to the West, written by Wú Chéng’ēn in the 16th century of the Ming Dynasty, is an influential work in Chinese culture. The main character of the novel, the Monkey King Sun Wukong, has become a highly popular character and been adapted into various cultural products. Sun Wukong’s popularity was adapted into three films directed by Cheang Pou-soi, namely Monkey King 1 (2014), Monkey King 2 (2016), and Monkey King 3 (2018). This article analyzes the reconfiguration of Sun Wukong in the films based on the monomyth schemes by Joseph Campbell, focusing on the construction of Sun Wukong’s heroic journey and his hybridity visualization that is closely related to his transformation from an archetypal hero who represents the principle of the “Three Teachings in One” to a modern superhero who represents social and individual values in the “Twelve Core Values of Chinese Socialism”. Through the archetypal theme of the journey, hybridity visualization, and a set of values associated with Sun Wukong, this article tries to analyze the transformation of his heroism from a classic hero into a modern superhero. The re-contextualization of this transformation to the contemporary China’s situation reflects the spirit of China today and its long journey from traditionalism to modernity.